Prediction of long-term functional outcome following different rehabilitation pathways after stroke unit discharge - Malin C. Nylén; Tamar Abzhandadze; Hanna C. Persson; Katharina S. Sunnerhagen (Medical Journals Sweden, 2024)
Objective: To investigate whether referral for different types of rehabilitation on discharge from Swedish stroke units can predict functional outcomes at 1 and 5 years after a stroke. Design: A longitudinal and registry-based study. Subjects/patients: A total of 5,118 participants with index stroke in 2011 were followed-up at 1 and 5 years after the stroke. Methods: Ordinal logistic regression models were developed to predict the category of functional outcome: independent, dependent, or dead. The primary predictors were planned rehabilitation in a home setting, inpatient rehabilitation, and outpatient rehabilitation, with no planned rehabilitation as the reference category. Results: Planned outpatient rehabilitation predicted independence (compared with death) at 1 year. Planned rehabilitation in the home setting predicted independence (compared with death) at 1 and 5 years. Compared with other planned pathways, participants planned for inpatient rehabilitation had more severe conditions, and planned inpatient rehabilitation did not predict independence. Conclusion: Planning for outpatient or home-based rehabilitation appeared to lead more effectively to participants achieving independence over the course of 1-5 years. This may have been due to the less severe nature of these participants' conditions, compared with those requiring inpatient rehabilitation.